Closing the Loop on Centralization of Cleft Care in the United Kingdom. (February 2018) - Ness, Andrew R.; Wills, Andrew R.; Waylen, Andrea; Smallridge, Jackie; Hall, Amanda J.; Sell, Debbie; Sandy, Jonathan R.
Objective: We highlight a major study that investigated the impact of reconfigured cleft care in the United Kingdom some 15 years after centralization. We argue that centralization as an intervention has a major impact on outcomes. Setting: Audit clinics held in Cleft Centers in the United Kingdom. Patients, Participants: Five-year-olds born between April 1, 2005, and March 31, 2007, with nonsyndromic unilateral cleft lip and palate. Interventions: Centralization of cleft care. Main Outcome Measure(s): We collected routine clinical measures (speech recordings, hearing, photographs, models, oral health, psychosocial factors) in a very similar way to a previous survey. Results: We identified 359 eligible children and recruited 268 (74.7%) to the study. Overall, their outcomes were better post-centralization. There have been marked improvements in dentoalveolar arch relationships and in speech whereas the prevalence of dental caries and hearing loss are unchanged. Conclusions: Centralized cleft care has changed UK outcomes considerably and there is no argument for returning to a dispersed model of treatment.